Silver nanoparticles – possible applications and threats - Kędzierska, Marta; Miłowska, Katarzyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2021)
Silver is known for its biocidal properties. This metal has been used for decorations and food preservation since ancient times and has also been used in medicine. Silver foil has been used to cover wounds and burns. In addition, silver solutions were created to help fight the microorganisms responsible for causing infections, which helped the wound healing process. Currently, to increase and optimize the properties of silver, it is used on a nanometric scale. Nanosilver, due to its expanded spectrum of properties, is used in many economic sectors, including in the production of disinfectants and food films, as well as in animal farms. Nanoparticles are also the basis of nanomedicine action. Creating new drug complexes with nanosilver and modifying the medical materials used in implantology or dentistry allow the lives of many people to be saved every day. In addition, nanosilver particles are commonly used as a specific disinfectant in the production of hospital materials: dressings, bandages, surgical masks, hospital clothing and shoes, and equipment. With the growing use of nanosilver, there are concerns about its harmful effects on living organisms, because not all its mechanisms of action are known. As is well known, the dose determines the toxicity of a given substance; the case is similar for nanosilver. However, is the dose providing antibacterial and antifungal properties non-toxic to animals and humans? This review presents a summary of the scientific research showing the scope of nanosilver activity and the resulting threats.